2020
DOI: 10.3390/en13153950
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Tall Onshore Hybrid Steel Wind Turbine Towers

Abstract: Increasing needs for taller wind turbines with bigger capacities, intended for places with high wind velocities or at higher altitudes, have led to new technologies in the wind energy industry. A recently introduced structural system for onshore wind turbine towers is the hybrid steel tower. Comprehension of the environmental response of this hybrid steel structural system is warranted. Even though life cycle assessments (LCAs) for conventional wind turbine tubular towers exist, the environmental performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The initial cost of this proposed rooftop PV system is $2770 (221,600 Tk). Thus, the overall profit during the full project life realised by switching from utility grid connection to rooftop solar PV system is $1131 (90,480 Tk). Accordingly, the payback period can be calculated using Equation (8):…”
Section: Cost Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The initial cost of this proposed rooftop PV system is $2770 (221,600 Tk). Thus, the overall profit during the full project life realised by switching from utility grid connection to rooftop solar PV system is $1131 (90,480 Tk). Accordingly, the payback period can be calculated using Equation (8):…”
Section: Cost Analysismentioning
confidence: 99%
“…Thus, interest is MECs and MFCs has been growing exponentially since the beginning of the 21st century although very few industrial applications exist nowadays due to the complexity of the maintenance of the proper conditions for the microbial population and the very low current rates. Although this technology is still not at an industrial-scale phase, some authors [90][91][92][93] point out its capacity to remove a mixed concentration of potential toxic elements from a contaminated influent, as the metal electroplate in the cathode chamber, with the advantage that they have very low energy needs. Moreover, as cells operate as MFCs, they can have a positive energy balance or, in the case of MECs, they can produce hydrogen or methane that can be used as bio-fuels [85,94].…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the latter solution, on-site welding has also been contemplated [70], which if realized would create new opportunities for a wide range of promising concepts. Hybrid solutions combining lattice and tubular parts have also been proposed [71,72].…”
Section: Introductionmentioning
confidence: 99%
“…Stavridou et al [11] examined ring stiffeners and vertical stiffening schemes to eliminate the presence of short wavelength buckles of the tower due to bending. Gkantou et al [12] performed the life cycle assessment of tall hybrid onshore steel wind turbine towers. Yadav and Gerasimidis [13] compared the wavy tower cylinder tower to make a more efficient design and concluded that the sensitivity of these towers is very small compared to that of the circular towers.…”
Section: Introductionmentioning
confidence: 99%